Evidence on the trade-off between corporate social responsibility and mergers and acquisitions investment. Issue 3 (August 2021) - Krishnamurti, Chandrasekhar; Shams, Syed; Chowdhury, Hasibul
In this article, we investigate whether there is a trade-off between corporate social responsibility (CSR) and mergers and acquisitions (M&A) investments. Consistent with conflict resolution view of stakeholder theory, our results document a negative relationship between CSR scores and M&A activity. We further show that the tendency of CSR firms' low engagements in M&A investmen ts is valid only for firms with no slack. We also find that firms choosing to trade off pay a lower bid premium to targets to create value for acquiring shareholders. These findings are robust to several alternative proxies and endogeneity tests. JEL Classification:G32, G34